An experimental hut evaluation of Olyset Plus, a long-lasting insecticidal net treated with a mixture of permethrin and piperonyl butoxide, against Anopheles fluviatilis in Odisha State, India. (December 2016) - Gunasekaran, Kasinathan; Sahu, Sudhansu; Vijayakumar, Tharmalingam; Subramanian, Swaminathan; Yadav, Rajpal; Pigeon, Olivier; Jambulingam, Purushothaman
Abstract Background Fast development of pyrethroid resistance in malaria vectors prompted the development of new vector control tools including combination of insecticides with different modes of action as part of resistance management strategies. Olyset Plus® is a new long-lasting insecticidal net, in which, permethrin and a synergist, piperonyl butoxide (PBO), are incorporated into filaments. Mixture nets such as this may have application against resistant mosquitoes, particularly those whose resistance is based on oxidative metabolism. There may also be enhanced activity against susceptible mosquitoes since mixed function oxidases are involved in a many metabolic activities including activation to form bioactive compounds. Methods Bio-efficacy of Olyset Plus was evaluated against susceptible malaria vector, Anopheles fluviatilis in experimental huts. Deterrence, blood feeding inhibition, induced exophily and killing effect were measured to assess the bio-efficacy. The results were compared with Olyset Net®, a polyethylene permethrin-incorporated LLIN and a conventionally treated polyester net (with permethrin) washed to just before exhaustion. Results Results showed significant reduction in entry (treatment: 0.4–0.8; control: 4.2 per trap-night) and increase in exit (56.3–82.9 % and 44.2 %) rates ofAnopheles fluviatilis in the treatment arms compared to control (P < 0.05). While blood feeding rates declined in treatment arms (18.8–30.6 %), it increased in control (77.6 %) (P < 0.05). This was further evident from the blood-feeding inhibition rates in treatment arms (60.6–90.6 %). Total mortality was significantly higher in all treatment arms (96.3–100 %) compared to control arm (2 %) (P < 0.05). Chemical analysis for active ingredient (AI) showed retention of 75 and 88 % in Olyset plus and Olyset net respectively after 20 washes. Performance of Olyset Plus washed 20 times was equal to the CTN and Olyset Net against the susceptible malaria vectorAn. fluviatilis, fulfilling the WHO efficacy criteria of Phase II evaluation for LLIN. However, the benefit of incorporating PBO and permethrin together in a long-lasting treatment could not be demonstrated in the current study as the target vector species was fully susceptible to pyrethroids. Conclusion Olyset Plus, with its intrinsic bio-efficacy could be an effective vector control tool to prevent transmission of malaria by susceptible vectors like An. fluviatilis . However, the results of the current study need to be further supported by testing the net at village level (Phase III) for community acceptability. Before taking the net to village level, it needs to be verified whether the net is better than pyrethroid nets in terms of bio-efficacy against resistant An. culicifacies, another malaria vector that has developed resistance to synthetic pyrethroids in India.